The thinking student's guide to college 75 tips for getting a better education - Roberts, Andrew Lawrence 1970- (Chicago guides to academic life, 2010)
Helps students take charge of their university experience by providing a blueprint they can follow to achieve their educational goals, whether at public or private schools, large research universities or small liberal arts colleges.